RADICAL SURGERY AND INTRAOPERATIVE RADIOTHERAPY WITH THE PHOTON RADIOSURGERY SYSTEM IN RECTAL CANCER: RETROSPECTIVE REVIEW OF 68 PATIENTS - I. B. Uvarov; M. V. Kazantseva; S. N. Potemin; I. N. Vasilenko; V. B. Kaushansky (Кубанский научный медицинский вестник)
The purpose of this study was to analyze the short-term and 1-year long-term results of the treatment including radical surgery and intraoperative radiotherapy (IORT) in patients with primary (PRC) and recurrent rectal cancer (RRC). We retrospectively reviewed 68 patients (pts.) treated with the Intrabeam Photon Radiosurgery System (PRS) following definitive resection of a locally advanced PRC or RRC. Gender distribution was 41 male and 27 female aged from 33 to 82 years (median 64.5). Stage II primary rectal cancer (PRC) was in 50 pts., stage III in 18 pts. RRC was found in 9 pts median follow-up after IORT was 9,6 months. Overall survival and disease free survival rate calculated using Kaplan-Meier analysis. A dose of 5.07Gy was prescribed to a depth of 1 cm (surface dose range was 9.4-17.0, median: 14.8 Gy). Median duration of IORT was 31.9 minutes (range: 15-36). Spheric applicators of 5 cm in diameter used in 40 cases and 4.5 cm - in 5 pts. No intraoperative or postoperative complications were attributed to IORT. Median discharge time after surgery was 17.7 days (range: 9-25). The 1-year overall survival rate was 90,1% (S.E.=4,9). The 1-year local recurrence free survival rate was 89,5% (S.E.=7,1). The 1-year distant metastasis free survival was 88,6% (S.E.=6,5). No cases of hydronephrosis or ureter fibrosis after IORT were documented. Fist experience suggests that Intrabeam PRS appears to be a safe technique for delivering IORT in rectal cancer patients. IORT with PRS marginally increased operative time, and did not appear to prolong hospitalization.